Size matters: identity of culturally important herrings in northeastern Brazil - Ferreira-Araújo, Thais; Lopes, Priscila Fabiana Macedo; Lima, Sergio Maia Queiroz (Ethnobiology and Conservation, 2021)
Fishery statistics are mainly made by recording the popular fish names, which is later translated into scientific identification. However, these names often either refer to a species group and/or vary along their distribution, increasing identification uncertainty. Species that have cultural value for traditional communities are known as culturally important species (CIS). Herein, we assessed Fishers’ Ecological Knowledge to investigate small-silvery herrings (ginga) used as part of a traditional dish com tapioca", that is recognized as a cultural heritage in the Brazilian northeastern. Through 103 interviews conducted in six communities in three states, we determined that ginga, although a name known elsewhere, is only traded as such in the metropolitan area of Natal. In this region, ginga is caught with drift net and deemed profitable by fishers. We identified both over- and under-differentiation, with ginga recognized by fishers as five, and sold as three main species, namely Opisthonema oglinum, Harengula sp., and Lile piquitinga. The larger specimens of two of those species (O. oglinum and Harengula sp.) were also traded as sardines. We found that most individuals sold as ginga were juveniles, which might impact the recruitment of some fish species. Due to its unique cultural relevance to the local community of Natal, ginga could be considered a CIS, which could aid future management or conservation measures.